Revolutionizing Green Minds: Unveiling Environmental Literacy of University Students in Oman - Al Aamri, Nihal Nasser Ghalib; Al Rashdi, Safiya Ahmed Ali; Thottoli, Mohammed Muneerali (Journal of Techno-Social, 2024)
Purpose: Students need to be environmentally literate  to understand the complex interactions between humans and the natural world and how human activity affects ecosystems. The importance of environmental literacy (EL) is growing, and without this understanding, students may have limited career options in sustainability, renewable energy, and conservation. Moreover, lacking EL, students can find it more difficult to contribute to creating eco-friendly technology and regulations. Hence, this study aims to explore the various dimensions of EL among university students in Oman.Methodology: This study gathered a sample of 238 students from universities in Oman to investigate the multidimensionality of EL. Following that, this study has employed structural equation modeling (SEM-PLS 4.0) software to analyze the collected data.Findings: The result showed that the environmental knowledge attributes have a significant relationship with the actual participation in environmental activities. Likewise, the results also confirmed that Interest in environmental activities has a significant relationship with actual participation in environmental activities.